Identifying entry points for adaptive governance in peri-urban Chennai (India): a multi-dimensional, multi-level, and multi-scalar approach - Woiwode, Christoph; Ramachandran, A.; Philip, Tarun; Rishika, D; Rajan, Sudhir Chella (Frontiers in Sustainable Cities, 2024)
Governing transitions have assumed increasing significance in managing change with respect to climate change and rapid periurbanization. In this respect, evidence from sustainability transitions research in South Asia stipulates the need for institutional innovations that are suitable to the governance context, which is characterized by a fuzzy field of “speculative frontiers,” and strong hierarchically structured mechanisms. This paper focuses on Chennai, India to ascertain the potentials of “adaptive governance” in this periurban region of the Global South. We approach this by (a) defining the periurban space from a bio-regional, socio-ecological systems perspective, (b) complementing it with a zonal classification considering disaster and climate change risks, and (c) presenting an adaptive governance framework. Based on analyzing existing governance structures, the paper discusses identified syndromes, synergistic potentials and activities for adaptive governance, especially highlighting water and agroecology-related pathways. Our integrated analytical approach is (a) multi-dimensional deploying the adaptive governance framework, (b) multi-level considering local, intermediate and state governance, and (c) multi-scalar applying macro, meso and micro scales. The implications underscore that transformative interventions, sooner or later, will have to challenge the system that produces such climate vulnerabilities. In spite of several barriers, there are noteworthy indications of adaptive governance practices discernible in numerous niche projects in the Chennai region that demonstrate diverse embryonic forms to build more strategic and conscientious approaches.